KONFORMITAS DAN KOHESIVITAS SEBAGAI MANAJEMEN KOMUNIKASI ANTARBUDAYA WARGA TIONGHOA DI KABUPATEN BOGOR - Agus Hitopa Sukma; Misnan Misnan; Iswahyu Pranawukir (Jurnal Pustaka Komunikasi, 2023)
The purpose of research is to know the cultural ethnic cohesiveness in the conformity of local wisdom, a study of social construction and management of intercultural communication among Chinese citizens in Bogor Regency. By using qualitative descriptive method and analysis, the several findings were obtained. First, in the Chinese Village of Inkopad-Inkopol, West Bogor, the cultural cohesiveness has been initiated since the colonial era, through a family approach. The conformity of local wisdom is shown by the involvement of ethnic Chinese in "abangan" Islamic worship. Second, in the Chinese Community Housing Cinere Depok, the cohesiveness is more visible on the socio-economic side. When the Chinese community shows their simplicity of living in a rural village, there is an interaction of closeness and togetherness. There is a kind of inclusiveness. The local cultural conformity is shown through the mixed of Chinese citizens in supporting social and cultural activities. Third, at the Wihara Amurwa Bhumi Cibinong, Chinese Ethnic Communication Forum, the Chinese are more dominant in showing their organizational character and ancestral culture that they continue to fight for. The cultural cohesiveness occured precisely in an exclusivity strategy. As a result, the exclusivity gave birth to uniqueness, which turned out to be a kind of tourist attraction for the surrounding community. This area is actually very well known for its ethnic performances.